Characterization and stability monitoring of maghemite nanoparticle suspensions - Nurdin, Irwan; Yaacob, Iskandar Idris; Johan, Mohd. Rafie; Bee , Chin Ang (Trans Tech Publications, Switzerland, 2012)
Maghemite nanoparticle suspensions were synthesized using a co-precipitation method and characterized by a variety of techniques including XRD, TEM, magnetic measurement, DLS, and zeta potential. The stability of the suspension was monitored by measuring the particle size distribution using DLS over a period of two months. The diffraction pattern from XRD measurement confirmed that the particles were maghemite with an average crystallite size of 9.4 nm. TEM observations and analyses showed that the geometry of maghemite nanoparticles were nearly spherical with a mean physical diameter of 9.9 nm. The maghemite nanoparticles showed superparamagnetic behavior with saturation magnetization value of 32.20 emu/g. The mean hydrodynamic diameter of the suspension remained unchanged after two months which indicated no formation of aggregation. The hydrodynamic diameters recorded were 45.1 nm and 48.4 nm, respectively. Additionally, lack of sedimentation indicated that the suspension was stable. The suspension’s zeta potential values were 41.5 mV and 40.4 mV for as synthesized and after two month of storage respectively.